2020
DOI: 10.1111/jfbc.13465
|View full text |Cite
|
Sign up to set email alerts
|

Human clinical trial to assess the effect of consumption of multigrain Indian bread on glycemic regulation in type 2 diabetic participants

Abstract: The efficacy of multigrain flatbread in regulating the lipid profile and carbohydrate homeostasis among type 2 diabetic patients was studied in 100 type 2 diabetic participants. The results revealed that the anthropometric parameters remained unaltered in both test and control groups. The fasting blood glucose levels (140.70 ± 8.43 versus 132.89 ± 5.63 mg/dl) did not significantly decrease. In contrast, the insulin levels (12.96 ± 1.06 versus 10.83 ± 1.03 μIU/ml) and HbA1c levels (8.01 ± 0.27 versus 7.40 ± 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Another study on finger millet consumption for 12 weeks (18) showed a significant reduction in IL-6 (from 4.9 ± 0.7 to 1.60 ± 0.5 mmol/l) (p = 0.000) and TNF-α (from 7.8 ± 1.2 to 3.9 ± 0.6 mmol/l) (p = 0.016). However, Sobhana et al (22) demonstrated that consumption of a millet-based diet for 3 months did not significantly reduce hs-CRP (from 0.45 ± 0.078 to 0.43 ± 0.064 µg/ml), which is not a significant reduction. More long-term studies are recommended to examine this effect.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Another study on finger millet consumption for 12 weeks (18) showed a significant reduction in IL-6 (from 4.9 ± 0.7 to 1.60 ± 0.5 mmol/l) (p = 0.000) and TNF-α (from 7.8 ± 1.2 to 3.9 ± 0.6 mmol/l) (p = 0.016). However, Sobhana et al (22) demonstrated that consumption of a millet-based diet for 3 months did not significantly reduce hs-CRP (from 0.45 ± 0.078 to 0.43 ± 0.064 µg/ml), which is not a significant reduction. More long-term studies are recommended to examine this effect.…”
Section: Discussionmentioning
confidence: 94%
“…Finger millet, foxtail millet, barnyard millet, and/or a mixture of millets (finger millet and little millet) were used in the 19 studies (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) that were included in one or more outcomes of meta-analysis. It was observed that consumption of milletbased food for a duration varying from 21 days to 4 months had a significant reducing effect on TC, triacylglycerol, VLDL-C, and/or LDL-C levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in pre-diabetic subjects, HbA1c levels fell to the normal reference level (from 6.65 ± 0.4 to 5.67 ± 0.4%) (12). The reduction is attributed to the high fibre content and low glycaemic index of the millet-based diet (11) which reduces the availability of glucose to form HbA1c and thereby regulates the HbA1c glycation process. It is evident that a millet-based diet has a positive effect on managing diabetes.…”
Section: Discussionmentioning
confidence: 94%
“…Many studies have demonstrated the efficacy of millets in improving glycaemic control, decreasing fasting, and postprandial rise in blood glucose concentration (7,8), reducing insulin index and insulin resistance and lessening glycosylated haemoglobin (HbA1c) level (8)(9)(10)(11)(12). Glycaemic index (GI) is a measure of how much the carbohydrate present in the food affects the rate and extent of change in post-prandial blood glucose concentration.…”
Section: Introductionmentioning
confidence: 99%